ANALISIS PEMBELAJARAN JARAK JAUH (PJJ) PADA MAHASISWA PGSD UMSU - Nadya Nadya; Despita Sari (EJoES (Educational Journal of Elementary School), 2021)
This study aims to analyze distance learning (PJJ) in UMSU PGSD students. This type of research is descriptive qualitative research subjects in semester III D. Data were collected using interview sheets. Data were analyzed by means of tianggulasi. The results of the study found that the impact of Distance Learning during the Covid 19 Pandemic on Umsu PGSD Class III D Students was effective enough to be carried out online where students were required to be more independent in obtaining their learning. The obstacles experienced when carrying out online-based distance learning activities experienced by UMSU PGSD Class III D students were the problem of a slow internet connection network so that they could miss the material from the lecturers. Thus Distance Learning (Online) becomes a solution as a substitute for face-to-face learning activities. Even though there are obstacles in implementing this Distance Learning, at least the learning is still running smoothly